Electrochemotherapy as a Trigger to Overcome Primary Resistance to Anti-PD-1 Treatment: A Case Report of Melanoma of the Scalp - Quaresmini, Davide; Di Lauro, Alessandra; Fucci, Livia; Strippoli, Sabino; De Risi, Ivana; Sciacovelli, Angela Monica; Albano, Anna; Achille, Gaetano; Montepara, Massimo; Russo, Sabino; Tassone, Gabriella; Guida, Michele (Frontiers in Oncology, 2021)
Background: Immunotherapy with immune checkpoint inhibitors is one of the main therapies for advanced melanoma. Nevertheless, albeit remarkable, immunotherapy results are still unsatisfactory as more than half of the patients progress, and resistance to treatment still has a dramatic impact on clinical outcomes. Local treatments such as radiotherapy or electrochemotherapy (ECT), in addition to local control with palliative intent, have been shown to release tumoral neoantigens that can stimulate a robust systemic antitumor immune response. Case presentation: We report the case of a patient with multiple nodular melanoma lesions of the scalp initially treated with local ECT. Soon after the procedure, multiple new lesions appeared close to the treated ones, therefore the patient started a systemic treatment with the anti-PD-1 nivolumab. The lesions of the scalp did not respond to immunotherapy, presenting a loco-regional spreading. To control the bleeding and painful lesions, we performed a second ECT, while continuing systemic immunotherapy. The treated lesions responded to the second procedure, while the other lesions continued progressing in number and dimension. Unexpectedly, after 2 months from the second ECT, the patient presented a progressive shrinkage of both treated and untreated lesions until complete remission. Concomitantly, he developed immune-related adverse events including grade 4 thyroid toxicity and grade 2 vitiligo-like depigmentation. At present, after 17 months from the first ECT and 13 months from the starting of antiPD-1 immunotherapy, the patient is in good clinical condition and complete remission of disease still persist without further side effects. Conclusion: This case highlights the potential role of ECT in increasing tumor immunogenicity and consequently in inducing a powerful immune response overcoming primary resistance to checkpoint inhibitor immunotherapy.